The Vulnerability Trends of the Banking Sector of Bangladesh: A Stress Testing Approach - Sarker, Niluthpaul; Nahar, Shamsun (International Journal of Economics and Financial Issues, 2018)
The study investigates the stress test report of the banks to assess the vulnerability of the banking sector as a whole on extreme but plausible shock scenarios. The regulatory pressure and extreme market competition bound the banking sector to assess their risk and show the sensitivity based on hypothetical extreme scenarios. It refers to the stability of the bank in disaster situations so that the economy can withstand negative externality by protecting the preventive measures. It is found that the bank credit is vulnerable and volatile due to higher defaults and more concentration. The mandatory practice of stress test will give better information to the market about the sensitivity of banks that will automatically adjust to the market value of the share. This is one of the techniques by which market gambling can be reduced. The study is emphasized its importance and mandatory practice in the market. Keywords: Bank Risk, Stress Test, Bangladesh. JEL Classifications: G2, G21